The Effect Of Managerial Ability And Career Planning On Job Satisfaction And Its Impact On Employee Performance - Muhammad Arif; Syahida Arsad; Muhammad Baqir Abdullah (Yayasan Riset dan Pengembangan Intelektual, 2022)
The general objective of this research study is to analyze the effect of managerial ability and career planning on job satisfaction in improving the employee performance of micro division of people business partners at PT. Bank BTPN Tbk. Pekanbaru Branch. This research study is quantitative research. The population of this research study was 71 employees at PT. Bank BTPN Tbk. Pekanbaru Branch. In collecting the data, this research study used Questionnaire. The instrumentof testing for validity used Guttman's formula while test instrument for reliability used Alpha formula from Cronbach. The test showed that it was valid and reliable. Hypothesis testing used normality, linearity, multicollinearity, path analysis, F-test, and T-test formulas. From the results of the research study it was found that: 1) there was an effect of managerial ability on job satisfaction with a path coefficient of 0.234; 2) there was the influence of career planning on job satisfaction with a path coefficient of 0.237; 3) there was an influence of managerial ability on employee performance with a path coefficient of 0.339; 4) there was an influence of career planning on employee performance with a path coefficient of 0.222; 5) there was an effect of job satisfaction on employee performance with a path coefficient of 0.208. From this research study, it was also found that there were 3 factors which influenced employee performance. The most influential factor was managerial ability while the smallest factor was career planning. Keywords: managerial ability, career planning, job satisfaction, and employee performance